The effect of using web-based Kahoot media on the learning outcomes of grade X students in informatics subject at MAN Sidrap - Dzulqarnain Dzulqarnain; Syamsunir Syamsunir; Muhammad Takdir (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the influence of using web-based Kahoot media on the learning outcomes of Grade X students at MAN Sidrap. Kahoot is a game-based learning application designed to enhance student engagement through interactive online quizzes. This research employed a quantitative method with a quasi-experimental design. The research sample consisted of two classes: the experimental class using Kahoot media and the control class using conventional teaching methods. The instrument used was a learning outcomes test. The analysis results showed that the average learning outcome of students in the experimental class was 75.29, while the control class had an average of 61.55. This difference indicates that the use of Kahoot media had a positive and significant effect on improving student learning outcomes. Kahoot was proven to create a more engaging, interactive, and competitive learning environment, thereby increasing student motivation and understanding of the material.